Social Learning Theory in Youth Sexual Behaviour Study in Central Java - Antono Suryoputro; Nicholas J Ford; Zahroh Shaluhiyah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background: Many public health researchers in Indonesia have advocated a greater role for the use of theory in strengthening the practice of research. However, public health researches and sexual & reproductive health researches in Indonesia have continued to focus primarilyon evaluating outcomes with less attention to the mechanisms by which these outcomes are produced. In this situation they argue that research is reduced to a set of predetermined steps that are mechanically applied to various interventions without concern for the theoretical implications of intervention content, setting, participants or implementing organizations. Such simple evaluations may provide a gross assessment of whether or not an intervention works under one set of conditions but fail to identify the reasons why (Brazil K., Ozer E., et all, 2005). As such, the conclusions are often less than satisfying to consumers of research resultsand not easily transferable to different settings.Method: The study applied a cross-sectional design, involving a total 2000 sample derived from youth population aged 18-24 years old, 1000 samples were each randomly selected from factory employers and university students in urban Central Java. The study employed quan-titative (survey) method using structured questionnaire as instrument and qualitative method (in-depth interviews and FGDs).Result : Although the findings of this cross-sectional study do not demonstrate that change in those factors/variables will reduce risk sexual behavior, they do suggest that future development and evaluation of sexual and reproductive health programs in youth population shouldtest the feasibility and the effect of changing those personal/cognitive and environment factors. Demonstrating causality would have required the experimental manipulation of self efficacy beliefs and a test of their effects on sexual behavior in a prospective rather than cross-sectional design. It is important to provide an open environment and counseling re-sources to the youth population in Central Java for strengthening youth self-efficacy which will increasing youth’s ability to avoid and/or reduce risky sexual behaviour. There is clearly a need for the reviewing of various laws, regulations, and policies at the central and regional level in order to develop more conducive environment for improving knowledge, attitude and practice of adolescent’s sexual lifestyleKeywords: Health services, Social Learning, Reproductive and sexual health, Sexual behaviour, Javanese youth.